The Basics of General, Organic, and Biological Chemistry - Ball, David W; Hill, John W; Scott, Rhonda J (Open textbook library., 2011)
The Basics of General, Organic, and Biological Chemistry by David W. Ball, John W. Hill, and Rhonda J. Scott is for the one-semester General, Organic and Biological Chemistry course. The authors designed this textbook from the ground up to meet the needs of a one-semester course. It is 20 chapters in length and approximately 350-400 pages; just the right breadth and depth for instructors to teach and students to grasp. In addition, The Basics of General, Organic, and Biological Chemistry is written not by one chemist, but THREE chemistry professors with specific, complimentary research and teaching areas. David W. Ball's specialty is physical chemistry, John W. Hill's is organic chemistry, and finally, Rhonda J. Scott's background is in enzyme and peptide chemistry. These three authors have the expertise to identify and present only the most important material for students to learn in the GOB Chemistry course. These experienced authors have ensured their text has ample in-text examples, and ”Test Yourself“ questions following the examples so students can immediately check their comprehension. The end-of-chapter exercises will be paired, with one answered in the back of the text so homework can easily be assigned and self-checked. The Basics of General, Organic, and Biological Chemistry by David W. Ball, John W. Hill, and Rhonda J. Scott is the right text for you and your students if you are looking for a GOB textbook with just the right amount of coverage without overdoing the concepts and overwhelming your students.